Operationalizing COVID-19 testing: Who, what, when, where, why, and how - Reddy, Anita J.; Fraser, Thomas G.; Grover, Purva; Weathers, Allison L.; Cruise, Michael; Foxx, Meredith A.; Babiuch, Christopher M.; Henricks, Walter H.; Meldon, Stephen W.; Muenzenmeyer, Ashleigh; Pengel, Shannon L.; Simon, James F.; et al. (Cleveland Clinic Journal of Medicine, 2020)
The authors review the rationale behind and approaches to testing for COVID-19, the quality of currently available tests, the role of data analytics in strategizing testing, and using the electronic medical record and other programs designed to steward COVID-19 testing and follow-up of patients.